Pengobatan Malaria di Perkotaan dan Pedesaan di Indonesia (Analisis Lanjut Riskesdas 2013) - Revi Rosavika Kinansi; Diana Andriyani Pratamawati; Rika Mayasari (Balai Penelitian dan Pengembangan Kesehatan Banjarnegara Badan Litbangkes Kemenkes RI, 2021)
Malaria control in Indonesia still against many challenges, especially in terms of malaria treatment. One of the causes of low coverage of Artemisin Based Combination Therapy (ACT) is that several locations are no longer malaria endemic, being negligent with malaria cases coming from endemic areas, so that patients are not immediately diagnosed as malaria patients. The purpose of this further analysis was to describe malaria treatment based on Plasmodium species associated with access, time, and administration of ACT treatment between urban and rural areas. The method used is descriptive analysis of secondary data from Basic Health Research in 2013 as many as 1,027,763 people by taking the unit of analysis of individuals who have been diagnosed with malaria by health personnel and individuals whose blood test results are positive for malaria. The results of the analysis provide information that in urban and rural areas, the treatment of P. falciparum and P. vivax is classified as good, namely the majority received ACT treatment, the time to receive ACT treatment was within the first 24 hours, and ACT treatment was given within 3 days of being drunk. However, it was found that in rural areas, P. vivax treatment was still not good because the majority did not receive ACT treatment. The implementation of malaria control in areas that are easily accessible and well-targeted are groups that can afford the costs involved in accessing targeted interventions by public subsidized programs. This encourages all regions to have good health services that provide better access to malaria control interventions.